2022
DOI: 10.1111/jfpp.17083
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of pullulan/paper/zein laminates as active food packaging materials

Abstract: Pullulan/paper/zein laminates were developed as food packaging materials with active properties, taking advantage of the hydrophilic character of the pullulan where the rockrose essential was incorporated as a bioactive agent to be more easily released into the packaged food; paper improved the general mechanical properties of the developed materials; and the hydrophobic nature of zein improved the barrier properties of the developed materials. A cohesive microstructure without a clear boundary between the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The color coordinates (L*, a*, and b*) and transparency of the films were measured using a Color Touch 2 spectrophotometer. The measurements were carried out using an observation angle of 10° and the illuminant D65 (daylight with a UV component), taking into account a number of random places on the films [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The color coordinates (L*, a*, and b*) and transparency of the films were measured using a Color Touch 2 spectrophotometer. The measurements were carried out using an observation angle of 10° and the illuminant D65 (daylight with a UV component), taking into account a number of random places on the films [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…To do this, test cups containing 15 g of anhydrous CaCl 2 as desiccant that had previously been dried at 105 °C were sealed with the films. The cups were then set at a temperature of 23 ± 2 °C and a relative humidity (RH) of 50 ± 5%, and the weight discrepancies were monitored every 2 h for a period of 48 h. The gradient was calculated using the linear regression’s slope of increasing weight with time [ 20 ]. The oxygen transmission rate (OTR) (cm 3 /m 2 .day) was evaluated using the equipment Labthink PERME ® OX2/23 (Labthink International, Medford, MA, USA) in accordance with ISO 15105-2:2003 [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shanmugan et al [ 193 ] reported that pullulan/graphene biocomposite coated on nanocellulose film improved the surface, barrier, and antimicrobial properties of the latter. In new research [ 194 ], the authors described the features of production of pullulan/paper/zein laminates as promising food packaging material. Another polysaccharide, hyaluronic acid, is known as a polymer used mainly in medicine, cosmetics, pharmaceutics, etc.…”
Section: Polysaccharides and Their Derivatives As Components Of Biode...mentioning
confidence: 99%